Deriving Costs of Service Use Among an Urban Homeless Population - Fuehrlein, Brian S. (2013)
The purpose of this study was to describe a novel approach to calculating service use costs across multiple domains of service for homeless populations. A randomly-selected sample of homeless persons was interviewed in St. Louis, MO and followed for two years. Service- and cost-related data were collected from homeless individuals and from the agencies serving them. Detailed interviews of study participants and of agency personnel in specific domains of service (medical, psychiatric, substance abuse, homeless maintenance, homeless amelioration services) were conducted using a standardized approach. Service utilization data were obtained from agency records. Standardized service-related costs were derived and aggregated across multiple domains from agency-reported data. Housing status was not found to be significantly associated with costs. Although labor intensive, this approach to cost estimation allows costs to be accurately compared across domains. These methods could potentially be applied to other populations.